Procedure in monitoring investigation information: case study of information management in Royal Malaysian Police / Widura Abd Kadir and Umi Asma’ Mokhtar - Abd Kadir, Widura; Mokhtar, Umi Asma’ (Faculty of Information Management, 2023)
Information monitoring is vital in information management because it enables the continuous maintenance of accountability and compliance. While the majority of information in police forces is typically associated with secrecy and non-disclosure, it has raised other concerns regarding investigation process accountability and police integrity. To avoid this, an investigation information monitoring framework (IIMF) is supposed to aid the monitoring team in carrying out their responsibilities and maintain the integrity. This study is monitoring the procedures of developing (input), utilizing (process) and the result of utilizing (output) investigation information. This paper discusses investigation information monitoring techniques used to identify anomalies in the investigation information, which will then be used to create the IIMF. The IIMF is expected to improve the efficiency of police investigative information management hence increasing police accountability through compliance.